The Influence of Consumer Reviews on Social Media on Purchase Intentions through a Digital Marketing Perspective - Eryana Setyarti; Juliani Pudjowati; Nurul Iman (Journal of Economic Education and Entrepreneurship Studies, 2025)
The rapid advancement of digital technologies has transformed consumer behavior, particularly in how purchase decisions are influenced by social media interactions. This study investigates the effect of consumer reviews on social media platforms on the purchase intentions of household products, with a focus on vendors and consumers at Pasar Turi Baru in Surabaya, Indonesia. Employing a quantitative research design, data were collected from 50 respondents through a structured questionnaire distributed on-site. The study utilized a simple linear regression analysis to examine the relationship between social media reviews and consumer purchase intentions. The results indicate that consumer reviews have a statistically significant positive effect on purchase intentions. Visual content, trustworthiness of the source, and user-generated authenticity emerged as key drivers influencing consumer confidence. The coefficient of determination (R²) reached 0.527, meaning that 52.7% of the variation in purchase intention can be explained by exposure to consumer reviews. Findings also highlight that visual testimonials and narrative experiences shared on platforms like Instagram and TikTok are particularly persuasive. This research offers practical implications for traditional vendors transitioning to digital marketing. It emphasizes the importance of leveraging user reviews, creating trustworthy content, and engaging with consumers online to enhance their purchasing motivation. The novelty of the study lies in its context: a traditional wholesale market integrating modern digital strategies, offering insights rarely explored in previous literature.